Adsorption in alumina pores open at one and at both ends1. Issue 6 (14th February 2015) - Bruschi, Lorenzo; Mistura, Giampaolo; Nguyen, Phuong T. M.; Do, Duong D.; Nicholson, David; Park, Sang-Joon; Lee, Woo
<x xml:space="preserve">Abstract</x> We have studied adsorption in regular, self-ordered alumina pores open at both ends and only at one end.